Communication theory & research : an ECJ anthology - McQuail, Denis; Golding, Peter, 1947-; Bens, Els de (SAGE, 2005)
This exciting collection of papers represents some of the finest communications research published over the last decade. To mark the 20th anniversary of the European Journal of Communication, a leading international journal, the editors have selected 21 papers, all of which make significant and valuable interventions in the field of media and communications. The volume is prefaced with an introduction by the editors and will be a central research text for scholars in this field.